NORIAN AMMONOIDS FROM THE NAYBAND FORMATION (IRAN) AND THEIR BEARING ON LATE TRIASSIC SEDIMENTARY AND GEODYNAMIC HISTORY OF THE IRAN PLATE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2018)
A Middle Norian (Alaunian 2) ammonoid assemblage from north of Esfahan (Central Iran) is described and chronostratigraphically evaluated. Formerly known as Distichites fauna, it represents a geographically widely distributed and stratigraphically important fossil level in the lower part of the Upper Triassic Nayband Formation. The new distichitid ammonoid genus Mesodistichites with the new species M. evolutus are introduced; additional faunal members are Noridiscites nodosus n. sp. and the leiostracean Stenarcestes diogenis and Pinacoceras cf. imperator. The Nayband Formation of the Esfahan region, belonging to the Zefreh-Soh Facies, is lithostratigraphically emended to contain three formally introduced members (Parsefid, Venher and Niazmargh members), which are all of Norian age, whereas Rhaetian sediments are missing. These members are correlated with Norian lithostratigraphic units of the type sequence of the formation in Nayband, eastern Iran. Integration of all Iranian Nayband data allows the recognition of three 3rd order sequences within this formation and the proof of a major pre- or syn-Jurassic unconformity across Central Iran and the Central-East Iranian Microcontinent (CEIM) related to the Main-Cimmerian event. Because of the latter and of major lithostratigraphic and facial differences, we propose to exclude the Nayband Formation from the Shemshak Group. A careful review of the available biostratigraphic data from northern and southern Iran let us further assume that the collision of the Iran Plate with Eurasia occurred in the later Early Carnian and was concurrent to the onset of the Carnian Humid Episode.